Methylene Blue and Lugol’s Iodine as an Adjunctive Tool for Early Diagnosis of Premalignant Oral Lesions - Surwaich Ali Channa,Arhama Surwaich,Muhammad Muslim Khahro, Uzma Tariq, Waqas Iqbal, Surwaich Ali Channa,Arhama Surwaich,Muhammad Muslim Khahro, Uzma Tariq, Waqas Iqbal (Journal of Rawalpindi Medical College, 2019)
Objective: To compare Methylene blue and Lugol’s Iodine as6an adjunctive tool6for early diagnosis of premalignant oral6lesions by taking histopathology as gold standard. Methods: In this cross-sectional study patients of oral0premalignant lesions were selected. Methylene blue and lugols iodine staining was used at lesion’s area. Mucosa0of target site was dried gently by gauze0and power0air0spray with triple syringe to make sure that the0lesion is not0being contaminated with0saliva. The dye was applied directly with a cotton0bud for 10-20 seconds and was decolorized. The dye retention pattern was evaluated by stain retention’s intensity on the lesion. Incisional biopsy was performed simultaneously from that site as gold standard. Results: Out of 60 cases, males were 81.6%. Majority (65.0%) had more than one addicting habit of mainpuri, gutka and supari. The commonest region of oral lesions was the buccal6mucosa (61.6%). According to the diagnostic accuracy of methylene blue the sensitivity was 89.4% and specificity was 66.6%. According to the Lugol’s Iodine sensitivity was 83.3% and specificity was 50%. Conclusion: Methylene blue and lugols iodine staining are an easy and non-invasive screening tools for the early diagnosis of malignancy.